The longest shot : Jack Fleck, Ben Hogan, and pro golf's greatest upset at the 1955 U.S. Open - Sagebiel, Neil (Thomas Dunne Books, 2012)
"With the overlooked Jack Fleck still playing the course, NBC-TV proclaimed that the legendary Ben Hogan had won his record fifth U.S. Open and signed off from San Francisco. Undaunted, the forgotten Iowan rallied to overcome a nine-shot deficit over the last three rounds--still a U.S. Open record--and made a pressure-packed putt to tie Hogan on the final hole of regulation play. The two men then squared off in a tense, 18-hole playoff from which Fleck emerged victorious in one of the most startling upsets in sports history. On par with the classic golf narratives of Mark Frost and John Feinstein, The Longest Shot will surprise and delight fans as they trace the improbable journey of an unheralded former caddie who played his way into the record books by out-dueling the sport's greatest champion of his time"--